On the new direction in the theory of gravitational lensing - Chechin, L.M.; Kurmanov, E.В. (Recent Contributions to Physics, 2019)
In this paper provides a brief overview of the state of the gravitational lensing problem. Its research, as the analysis of the literature shows, can be divided into three parts. The first is studying gravitational lenses within the solar system, the second is gravitational lenses on the scales of galaxies and their clusters, the third is the study of gravitational lenses on the scales of the Universe. We note that further study of gravitational lensing on the scales of galaxies and their clusters should be considered taking into account the presence of dark matter halo, including its non-stationary nature.